THE NARCOTICS ABUSE TERM WEAKNESSES IN CRIMINAL LAW ENFORCEMENT OF INDONESIA - Elpina Elpina; Mariah Sonanggok Purba (UNISSULA, 2021)
A crime of narcotics abuse has experienced an alarming development, one of which is the increasing factor of narcotics abuse, one of which is the legal vacuum in law enforcement against drug abuse. The approach method used uses a normative juridical approach, the research results obtained are the weaknesses of narcotics criminal law enforcement include: (a) in the formulation of criminal sanctions, namely most of the criminal sanctions in Act No. 35 of 2009 are formulated cumutatively, in the formulation of the most cumulations are between imprisonment and sufficient fines. large, there are no special rules for corporations that do not pay fines, and no specific types of sanctions (criminal / action) are seen for corporations (b) related to the issue of criminal threats, namely: there are offenses that are given a special minimum criminal threat which is If there is a deviation from the Criminal Code system, there are no specific guidelines or regulations for the application of minimum penalties, and there are no specific criminal rules to implement the minimal system can be a problem if there is participation, trial, discourse, recidive, criminal mitigation, expiration, and so on.